What to do to get good electricity prices? - Linares, Pedro (Razón y fe, 2021)
The significant increase in the price of electricity that Europe and particularly Spain has been suffering in the last months has produced, besides social unrest, a heated discussion about the policy measures required to mitigate it. In this short paper, I assess the main proposals, and I put forward a set of general principles that should be followed for the electricity price to be fair and efficient, looking at each of its components.